The Lived Experience of Siblings of Children With Cancer Who Attended a Peer Support Camp in the United States. (July 2022) - Gregory, Donna; Van Puymbroeck, Marieke; Crowe, Brandi; Garst, Barry; Amylon, Michael
Childhood cancer has a profound and negative impact on siblings, yet there are limited studies exploring lived experiences from their perspective. This qualitative study examined the perceptions and experiences of siblings of children with cancer who attended a peer support camp. Semi-structured interviews were conducted three to six weeks after the weeklong peer support camp with a stratified random sample of 10 siblings (six non-bereaved and four bereaved) ages 8 to 16 years. The qualitative data were analyzed using conventional content analysis and an inductive data-driven approach. Four themes emerged: social connection (subthemes: support/feeling of belonging, mentorship, and expressing feelings), personal growth, identity, and freedom to have fun and relax. These findings add to the scant body of research by providing enhanced understanding of the siblings' experiences and new insights into their perceptions of meaning and outcomes associated with participation in a peer support camp. These findings have implications for peer support camp programs and the well-being of siblings of children with cancer.